Stable and Ultrafast Blue Cavity‐Enhanced Superfluorescence in Mixed Halide Perovskites - Linqi Chen; Danqun Mao; Yingjie Hu; Hongxing Dong; Yichi Zhong; Wei Xie; Nanli Mou; Xinjie Li; Long Zhang (Advanced Science, 2023)
Abstract Cavity‐enhanced superfluorescence (CESF) in quantum dot (QD) system is an ultrafast and intense lasing generated by combination of quantum coupling effect and optically stimulated amplification effect, which can provide a new idea for realizing high quality blue light sources and address the limitation of conventional inefficient blue light sources. Modifying halide composition is a straightforward method to achieve blue emission in perovskite QD system. However, the spectral instability introduced by photoinduced halide phase segregation and low coupling efficiency between QDs and optical cavities make it challenging to achieve stable blue CESF in such halide‐doped QD system. Herein, long‐range‐ordered, densely packed CsPbBr2Cl QD‐assembled superlattice microcavities in which the two core issues can be appropriately addressed are developed. The QD superlattice structure facilitates excitonic delocalization to decrease exciton‐phonon coupling, thus alleviating photoinduced phase segregation. By combination of theoretical analysis and temperature‐dependent photoluminescence (PL) measurements, the underlying photoinduced phase segregation mitigation mechanism in mixed halide superlattices is clarified. Based on the CsPbBr2Cl QD superlattices with regularly geometrical structures, in which the gain medium can be strongly coupled to the naturally formed microcavity, stable and ultrafast (3 ps) blue CESF with excellent optical performance (threshold ≈33 µJ cm−2, quality factor ≈1900) is realized.